An electrochemical sensor for the sensitive determination of phenylethanolamine A based on a novel composite of reduced graphene oxide and poly(ionic liquid). Issue 1 (1st December 2014) - Li, Jinchun; Li, Qian; Zeng, Yanbo; Tang, Ting; Pan, Yangdan; Li, Lei
Abstract : The preparation for a novel composite of RGO–PIL and its electrochemical sensor for sensitive detecting phenylethanolamine A. Abstract : In this paper, we report an electrochemical sensor for phenylethanolamine A (PEA) that is based on a novel composite of reduced graphene oxide and poly(ionic liquid) (RGO–PIL). The RGO–PIL composite was prepared by radical polymerization of 1-vinyl-3-ethylimidazolium tetrafluoroborate monomer on graphene matrix. The RGO–PIL composite was characterized by Fourier transform infrared spectroscopy, thermal gravimetric analysis, scanning electron microscopy, Raman spectroscopy and X-ray diffraction. The RGO–PIL sensor involved advantages such as a good electrocatalytic property and large surface area. Due to the synergistic contribution of RGO and PIL, the RGO–PIL sensor can be applied for detecting PEA with high sensitivity. In addition, compared with the PIL sensor and bare electrode, the RGO–PIL sensor had the highest peak current response for PEA. Under the optimal experiment conditions, the reduction peak current was proportional to the concentration of PEA from 0.005 to 10.0 μM with the detection limit of 0.002 μM. Owing to the electrochemical reduction of nitro group for PEA, 1000-fold of clenbuterol, ractopamine, and salbutamol did not interfere with PEA determination based on RGO–PIL sensor. The RGO–PIL sensor not only exhibited good stability with adequate reproducibility and accuracy, but also demonstrated efficiency in the determination of PEA for pig urine samples.